2008
DOI: 10.1111/j.1475-2743.2008.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Soil penetration resistance and tree root development

Abstract: Current UK guidance suggests that a ‘rootable’ soil profile of at least 1.0 m depth should be sufficient to allow adequate rooting of the majority of tree species in a range of soil types and climatic conditions [Arboricultural Journal (1995) vol. 19, 19–27]. However, there is some uncertainty as to what constitutes a loosened soil profile in terms of penetration resistance. In this study the root development of Italian alder, Japanese larch, Corsican pine and birch was assessed after 5 years of tree growth. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 15 publications
1
44
0
3
Order By: Relevance
“…and birch (Betula pendula Roth. ; Sinnett et al 2008). Plants may exhibit compensatory growth as they respond plastically to localised areas of compaction, this response varying between species (Bingham and Bengough 2003).…”
Section: Soil Texture and Compactionmentioning
confidence: 99%
“…and birch (Betula pendula Roth. ; Sinnett et al 2008). Plants may exhibit compensatory growth as they respond plastically to localised areas of compaction, this response varying between species (Bingham and Bengough 2003).…”
Section: Soil Texture and Compactionmentioning
confidence: 99%
“…The cone resistance also serves as an indicator of the root penetration and root growth capabilities (Materechera and Mloza-Banda 1997). Sinnett et al (2008) reported that a soil having a cone resistance larger than 3 MPa caused a major hindrance for the root penetration of four tree species (Japanese larch, Italian alder, birch, and Corsican pine) in the sandy loam soils as shown in Fig. 5; nearly all roots (90.7%) were present in the soil with a cone resistance class less than 3 MPa.…”
Section: Soil Strengthmentioning
confidence: 99%
“…5 Mean percentage of roots in each penetration resistance class using the penetrometer; 90.7% of roots are present in penetration resistance class less than 3 Mpa. From Sinnett et al (2008) the soil organic carbon and nitrogen in the soil (De Neve and Hofman 2000). In a laboratory experiment, when silt loam (acid forest soil) was compacted artificially to a bulk density of 1.5 from 1.1 Mg/m 3 , a significant reduction in the carbon mineralization and net nitrification rates was observed after 9 months (Tan and Chang 2007).…”
Section: Carbon and Nitrogen Cyclesmentioning
confidence: 99%
“…This effect is directly associated with the reduction in the availability of water in the soil, soil aeration, and nutrients to plants, along with the increase of soil resistance to root growth (LETEY, 1985;MEDEIROS et al, 2010). Among various methods to determine the state of soil compaction and physical quality, the evaluation of soil penetration resistance (SPR) has been commonly used in experimental studies, not only related to precision agriculture (SILVA et al, 2004;BOTTEGA et al, 2011;CHERUBIN et al, 2011;DALCHIAVON et al, 2011;GIRARDELLO et al, 2011) but also to assessments of management conditions of agricultural areas (GOEDERT et al, 2002;NEIRO et al, 2003;FREDDI et al, 2007;SILVA et al, 2009;CALONEGO & ROSOLEM, 2011;OTTO et al, 2011) and forests (SEIXAS & SOUZA, 2007;SINNETT et al, 2008).…”
Section: Introductionmentioning
confidence: 99%